2011
DOI: 10.2298/gabp1172087g
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical and mechanical properties of the Struganik limestone (Vardar zone, Western Serbia)

Abstract: The Struganik limestone has been increasingly popular in recent years for interior and exterior building applications, due to easy workability, low cost and multi purpose suitability. The quality of limestone is determined by its mineralogical and textural characteristics and physico-mechanical properties. The Struganik stone corresponds to marl, clayey limestone and limestone (micritic and allochemical). The limestone is commonly layered, either thinly bedded or banked. Chert concretions are present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Vásárhelyi [11] reported a 74% reduction in uniaxial compressive strength of the Miocene limestone and 53% reduction in modulus due to saturation. Similarly, Rajabzadeh et al [12] and Gajic et al [13] reported a 70% and 10% reduction in uniaxial compressive strength of carbonate rocks and limestones due to saturation, respectively. Mann and Fatt [14] conducted a series of compression tests on sandstones and found that modulus could be reduced by 6∼19% for the saturated samples.…”
Section: Introductionmentioning
confidence: 87%
“…Vásárhelyi [11] reported a 74% reduction in uniaxial compressive strength of the Miocene limestone and 53% reduction in modulus due to saturation. Similarly, Rajabzadeh et al [12] and Gajic et al [13] reported a 70% and 10% reduction in uniaxial compressive strength of carbonate rocks and limestones due to saturation, respectively. Mann and Fatt [14] conducted a series of compression tests on sandstones and found that modulus could be reduced by 6∼19% for the saturated samples.…”
Section: Introductionmentioning
confidence: 87%
“…Massive travertine with less porosity has a higher UCS, while more porous laminated travertine has a lower UCS. Studying the petrophysical and mechanical properties of Struganik limestone, Gajic et al [20] reported a 10 % decrease in UCS due to saturation. They also noted that the UCS reduction in Struganik limestone was only 5 % after 25 freeze-thaw cycles.…”
Section: Shale/mudstonementioning
confidence: 99%
“…Apart of the reduction of the durability associated with water transport inside the microstructure due to the abovementioned weathering processes, the mechanical parameters of porous building stones are frequently subjected to important variations depending on their water content (Wong, Maruvanchery, & Liu, 2016). In this connection, several researches have shown that water saturation of rock materials can cause significant decreases of some of their most important mechanical properties such as unconfined compressive strength (UCS) or static Young´s modulus (E st ) (Erguler & Ulusay, 2009;Gajic, Matovic, Vasic, & Sreckovic-Batocanin, 2011;Hawkins & McConnell, 1992;Karakul & Ulusay, 2013;Lin, Jeng, Tsai, & Huang, 2005;Rabat, Cano, Tomás, Tamayo, & Alejano, 2020;Shakoor & Barefield, 2009;Török & Vásárhelyi, 2010;Vásárhelyi, 2005;Verstrynge, Adriaens, Elsen, & Van Balen, 2014). Furthermore, it has been recently observed that other mechanical parameters like Brazilian Tensile Strength (BTS), Point Load Strength Index (I s(50) ), shear strength parameters (cohesion and internal friction angle) or dynamics properties are also significantly reduced when the effective pore network of geomaterials is completely filled of water (Gholami & Rasouli, 2014;Kahraman, 2014;Karakul & Ulusay, 2013;D.…”
Section: Introductionmentioning
confidence: 99%